The effect of youtube video in students’ listening comprehension of the tenth-grade students of MAN 2 Kota Madiun - Agus Setiawan; Erlik Widiyani Styati; Vita Vendityaningtyas (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
This study aims to analyse the effect of listening skills on tenth-grade students by using YouTube video media. The method used in this study is quantitative using a quasi-experimental design. This research was conducted at MAN 2 Kota Madiun using the tenth grade sample as the object of research and 68 students from both classes. The Researcher used a listening test to collect data. In analysing the data, the technique used is independent t-test to determine the effect of media use. The results showed that there was a significant effect on listening comprehension in the experimental class between the control class. Students who are taught by YouTube video teaching media have higher scores than students who are taught using conventional teaching. The results obtained that the significance value of equal variances is assumed to be 0.000, so it can be concluded that this significant value is less than 0.05 (0.000 < 0.05). This means that YouTube video provide many benefits for students in their listening skills.